Unforeseen progressive outer retinal necrosis in a child following bone marrow transplant. Issue 1 (6th January 2021) - Sachan, Anusha; Lata, Suman
Abstract : A 10-year-old boy underwent stem cell transplant for Hodgkin's lymphoma and developed vomiting and seizure in the postoperative period. An ophthalmic referral was made from intensive care unit, to rule out papilledema. On examination, there was no papilledema in both eyes, instead there were areas of retinal necrosis with no haemorrhages or vitritis in right eye. Cerebrospinal fluid serology was negative for herpes but MRI showed hyperintensity in temporal lobe. A clinical diagnosis of progressive outer retinal necrosis (PORN) was made and fundus picture was documented with help of a smartphone and 20D lens. High-dose intravenous injection acyclovir was started and PORN lesion improved on treatment.